A qualitative examination of factors shaping high and low exposures to hazardous air pollutants among Hispanic households in Miami. Issue 10 (3rd October 2017) - Rocha, Jonathan I.; Grineski, Sara E.; Collins, Timothy W.
ABSTRACT: Hispanic residents suffer disproportionately from exposure to toxic pollution hazards, but little is known about why some Hispanic residents live in high-risk neighbourhoods while others are protected from similar risks. This study uses comparative interview-based methods to further understanding of Hispanic people's residential decision-making and their associated exposures to hazardous air pollutants (HAPs) in the Miami Metropolitan Statistical Area (Florida), which is home to one of the most diverse Hispanic populations in the U.S. We use 22 in-depth interviews conducted with Hispanic householders living at high and low risk to HAPs, selected from a larger representative phone survey of 650 local residents. For Hispanic households at high risk, economic constraints, family ties, desiring a central location, a sense of community, and comfort in a shared culture contributed to their residences in high risk locations. In contrast, protective factors for Hispanic households living at low risk included the desire to live in an ethnically diverse setting, the ease of finding service work, and preferring environmental amenities and exclusivity. Findings demonstrate that there are considerable differences in factors shaping residential decision-making of low- and high-risk Hispanic residents, but that all were influenced by economic, socio-cultural, and environmental considerations to varying degrees.